Autoimmune polyglandular syndrome type 3 (APS-3) among patients with premature ovarian insufficiency (POI). (August 2016) - Szlendak-Sauer, Katarzyna; Jakubik, Daniel; Kunicki, Michał; Skórska, Jolanta; Smolarczyk, Roman
Abstract: Objectives: Autoimmune polyglandular syndrome type 3 – (APS-3), is defined as the coexistence of autoimmune thyroiditis with other non-ovarian autoimmune diseases without primary adrenal insufficiency. Additionally the definition of APS-3 also includes primary ovarian insufficiency (POI) coexistence with autoimmune thyroiditis. The main goal of that study is to assess the prevalence of APS-3 defined as coexistence of autoimmune thyroiditis with POI in population of 46 XX karyotype women with primary ovarian insufficiency (POI). The second goal is to investigate hormonal profile and insulin sensitivity in women with POI and subgroups of women with APS-3 – POI/APS-3(+) and without APS 3 – POI/APS-3(−). Materials and methods: Anthropometric measurements, coexistence of autoimmune diseases, androgens, fasting glucose and insulin, glucose and insulin at 60′ and 120′ of oral glucose tolerance test (OGTT) and homeostasis model for insulin resistance (HOMA-IR), were determine in 98 patients aged between 18 and 39 with spontaneous 46 XX primary ovarian insufficiency (POI), in 33 POI/APS-3(+), 65 POI/APS-3(−), and 75 healthy controls. Results: Continuous data were summarized by the mean ± standard deviation (SD), and categorical data by number (percentages). Data were checked for normality using Shapiro–Wilk test, the comparison between groups were performed using non-parametric Mann–Whitney or Kruskall–Wallis test. Pearson's correlation coefficient was used to assess the relationships between parameters. Statistical significance was defined as p values <0.05. Autoimmune thyroid disease (ATD) was presented in 33/98 (33.7%) patients with POI. The groups did not differ significantly in respect to age and body mass index (BMI). Women with POI, POI/APS-3(+) and POI/APS-3(−) showed significantly lower serum androgens in comparison to controls. Additionally women with POI/APS-3(+) showed hyperinsulinemia after 1 h of OGTT; No significant differences in serum fasting glucose, insulin and during 2 h OGTT between groups were observed. Conclusions: The prevalence of APS-3 is 33.7% in patients with spontaneous 46 XX primary ovarian insufficiency. Women with POI, POI/APS-3(+) and POI/APS-3(−) feature lower testosterone, androstendione, dehydroepiandrostendione sulphate in comparison to controls. Women with POI/APS-3(+) could have hyperinsulinemia and should be carefully evaluated for metabolic disorders.